1983
DOI: 10.1016/s0022-5347(17)51670-5
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Group for Benign Prostatic Hypertrophy

Abstract: A case control study was conducted on 100 patients with benign prostatic hypertrophy (BPH) and 100 controls matched by age and residence. Interviews were performed by welltrained urologists using an original questionnaire. Matched-pair analysis revealed the following characteristics and relative risks (RR) as being significantly (P < 0.05) different among the BPH patients versus the controls: higher educational background (RR = 2.77); not engaged in farming, forestry, or fishing (RR = 4.82); no environmental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
0
3

Year Published

1993
1993
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 8 publications
(8 reference statements)
6
30
0
3
Order By: Relevance
“…For example, casecontrol studies have demonstrated that men who consume fruits and vegetables rich in vitamin C have a lower incidence of BPH [13,14]. Furthermore, vitamin C plasma concentrations were found to be significantly lower in BPH patients than in normal healthy controls [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, casecontrol studies have demonstrated that men who consume fruits and vegetables rich in vitamin C have a lower incidence of BPH [13,14]. Furthermore, vitamin C plasma concentrations were found to be significantly lower in BPH patients than in normal healthy controls [15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating the relation between alcohol and clinically detected or symptomatic BPH have not been consistent, with some finding a positive relation (20,21) and others no relation (19,22). Numerous studies have evaluated the relation between smoking and either surgery for BPH (14)(15)(16)(17)(18)(19)(23)(24)(25)(26)(27) or clinically detected or symptomatic BPH (19-22, 25, 27-29) and generally have shown a moderate inverse association with current smoking or no effect of smoking.…”
mentioning
confidence: 99%
“…Araki et al, in their case-control study of 100 Japanese men with symptomatic benign prostatic enlargement (BPE) and 100 healthy controls, found the relative risk of symptomatic BPE to be higher among those who ate meat daily; the relative risk was 2.1 (statistically not significant) (1). They also found that the relative risk of symptomatic BPE was increased (statistically significantly) among men who consumed milk, who consumed green and yellow vegetables irregularly and who did not consume pickles at every meal.…”
mentioning
confidence: 99%